miR-616-5p Promotes Invasion and Migration of Bladder Cancer via Downregulating NR2C2 Expression - Ren, Wenbiao; Hu, Jiao; Li, Huihuang; Chen, Jinbo; Ding, Jian; Zu, Xiongbing; Fan, Benyi (Frontiers in Oncology, 2021)
Background: MicroRNAs, small non-coding RNA molecules with about 22 nucleotides in length, play a significant role in the development of bladder cancer. Previous studies found that miR-616-5p could promote the progress of cancers. However, it’s role in bladder cancer remains unclear. In the study, we aimed to demonstrate how miR-616-5p impact invasion and migration of bladder cancer and its potential downstream target. Methods: Firstly, qRT-PCR was used to detect the expression of miR-616-5p in normal bladder uroepithelial cell line and bladder cancer cell lines. Then, Chamber-Transwell invasion and would healing migration assays were used to detect the roles of miR-616-5p and NR2C2 in invasion and migration. Subsequently, Western blot was used to evaluate the regulation effects of miR-616-5p and NR2C2. Finally, Luciferase assays were performed to manifest the mechanism of miR-616-5p and NR2C2 regulation. Results: We found miR-616-5p was upregulated in bladder cancer and it could promote the invasion and migration of bladder cancer in vitro. Moreover, we demonstrated that NR2C2 was a downstream target of miR-616-5p. MiR-616-5p could inhibit the expression of NR2C2 by binding to the 3’UTR of NR2C2 mRNA. Importantly, patients with high expression of NR2C2 showed better prognosis in bladder cancer. Conclusions: This study identifies miR-616-5p can promote bladder cancer progression via altering the expression of NR2C2. Therefore, identifying miR-616-5p expression levels might be a useful strategy for developing potential therapeutic targets in bladder cancer.